Efek Penggunaan Tepung Daun Ubi Jalar Ungu Dan Tepung Daun Ubi Jalar Kuning Terhadap Karakteristik Fisikokimia, Organoleptik Dan Aktivitas Antioksidan Pada Cookies - Olga Olivia Maretta; Sukardi Sukardi; Sri Winarsih (Universitas Muhammadiyah Malang, 2021)
Abstract. Utilization of sweet potato as a food product has been commonly carried out and the nutrients in it have been known. This is what underlies the existence of food diversification using sweet potato leaves. Sweet potato leaves contain B vitamins, iron, calcium, zinc and protein, besides that sweet potato leaves are a source of natural antioxidants such as β-carotene, anthocyanins, phenolic acids, tannins, polyphenols, including lutein. Utilization of sweet potato leaves into processed products, one of which is by flouring sweet potato leaves as a substitute for cookies. The research design was carried out using a random nested block design, consisting of two factors. The first factor as a nest was purple sweet potato leaves and yellow sweet potato leaves. Second factor as a nesting factor is the formulation of cookies with the substitution of sweet potato leaf flour with different levels (3.3g, 6.6g, 9.9g, 13.2g). Observation parameters include moisture content, ash content, fat content, protein content, total carbohydrates, antioxidant activity, texture, organoleptics (taste, color, preferences, aroma, aftertaste). The results of this study indicate an effect on ash content and protein content in different varieties. In the treatment of different formulations, it is known that there is an effect on moisture, carbohydrate, and protein content. The effect of adding purple sweet potato leaf flour and yellow sweet potato leaf flour in this study affected organoleptics including taste, color, aroma, preferences, and aftertaste. The treatment of cookies with the addition of sweet potato leaf flour with the highest ash content was 2.83%, the lowest water content was 1.51%, the highest protein content was 31.07%, and the largest carbohydrate content was 41.04%. Keywords: antioxidant, processed, sweet potato leaves Abstrak. Pemanfaatan ubi jalar sebagai produk pangan telah umum dilakukan dan telah diketahui zat gizi didalamnya. Hal inilah yang mendasari adanya diversifikasi pangan dengan menggunakan daun ubi jalar. Daun ubi jalar mengandung vitamin B, zat besi, kalsium, zinc dan protein, selain itu daun ubi jalar merupakan sumber antioksidan alami seperti ß-carotene, antosianin, asam fenolik, tannin, polifenol, termasuk lutein. Pemanfaatan daun ubi jalar menjadi produk olahan, salah satunya dengan menepungkan daun ubi jalar untuk substitusi cookies. Penelitian ini menggunakan Rancangan Acak Kelompok Tersarang (Nested) terdiri atas dua faktor. Faktor 1 sebagai sarang yaitu jenis daun, faktor 2 sebagai faktor yang tersarang yaitu formulasi dengan level yang berbeda (3,3g, 6,6g, 9,9g, 13,2g). parameter pengamatan meliputi kadar air, kadar abu, kadar lemak, kadar protein, karbohidrat total, aktivitas antioksidan, daya patah, dan organoleptic (rasa, aroma, warna, aftertaste, dan skoring). Hasil dari penelitian ini diketahui bahwa adanya pengaruh dari penggunaan jneis daun ubi jalar yang berbeda meliputi kadar abu dan kadar protein sedangkan pengaruh dari formulasi terhadap karakter fisikokimia meliput kadar air, kadar karbohidrat dan protein. Pada organoleptiknya jenis maupun formulasi berpengaruh nyata terhadap rasa, warna, skoring, aftertaste, dan aroma. Kata kunci: antioksidan, cookies, daun ubi jalar ungu dan daun ubi jalar kuning